Analytical study of some antidiabetic agents - Asmaa Abdelkerim Mandour; Hany Mohamed Safwat; Ramzia Ismail Elbagary; Samy Emara (Cairo : Asmaa Abdelkerim Mandour, 2010)
In this study methods of anaysis of two antidiabetic drugs namely Pioglitazone hydrochlorude (PG ) and Rosiglitazone maleate (RSG ) are proposed . The drugs were analysed in their pure from in laboratory prepared mixtures with their degradation products in pharmaceutical dosage forms and in biological fluid .
Thesis (M.Sc.) - Cairo University - Faculty of Pharmacy - Department of Pharmaceutical Chemistry
Issued also as CD
Keywords: {u2206}A (differential methods ); PG (Pioglitazone hydrochloride ); RSG (Rosiglitazone maleate )